Incidence and risk factors for life‐threatening bleeding after allogeneic stem cell transplant. (26th March 2015) - Labrador, Jorge; López‐Corral, Lucia; Vazquez, Lourdes; Sánchez‐Guijo, Fermin; Guerrero, Carmen; Sánchez‐Barba, Mercedes; Lozano, Francisco S.; Alberca, Ignacio; del Cañizo, María C.; Caballero, Dolores; González‐Porras, Jose R.
Summary Bleeding is a frequent complication after allogeneic haematopoietic stem cell transplantation (HSCT) and may affect survival. The purpose of this study was to determine the incidence and risk factors for life‐threatening bleeding after HSCT by retrospective evaluation of 491 allogeneic HSCT recipients. With a median follow‐up of 33 months, 126 out of 491 allogeneic HSCT recipients experienced a haemorrhagic event (25·7%) and 46 patients developed a life‐threatening bleeding episode (9·4%). Pulmonary and gastrointestinal bleeding were the most common sites for life‐threatening bleeding, followed by central nervous system. In multivariate analyses, the presence of severe thrombocytopenia after day +28 and the development of grade III–IV acute graft‐versus‐host disease (GVHD) or thrombotic microangiopathy (TMA) retained their association with life‐threatening bleeding events. The overall survival at 3 years among patients without bleeding was 67·1% for only 17·1% for patients with life‐threatening bleeding (P < 0·001). In conclusion, life‐threatening bleeding is a common complication after allogeneic HSCT. Prolonged severe thrombocytopenia, acute grade III–IV GVHD and TMA were associated with its development.